Evaluation of fibroblast growth factor-23 and alpha klotho levels in patients with sarcoidosis - Özen Engin, Esra; Sav, Tansu; Öneç, Kürşat; Arbak, Peri Meram (International Journal of Research in Medical Sciences, 2024)
Background: Sarcoidosis is a systemic granulomatous disease. In its pathology, it is thought that 1-alpha hydroxylase production and activation as well as 1,25-hydroxy vitamin D production from active macrophages take place. FGF-23 and alpha klotho are proteins that play a key role in the bone-parathyroid-kidney axis, regulation of phosphate and calcium metabolism, and vitamin D metabolism. We aimed to demonstrate the effects of pathologic conditions on bone metabolism and the occurrence of vascular calcification since vitamin D can be activated in non-kidney patterns and hypercalcemia and hypercalciuria can be seen in these patients. Methods: The study was designed as a prospective case-control study. The study included 42 patients with sarcoidosis and 41 healthy volunteers who were admitted to Düzce University Medical Faculty Hospital. Age, gender, comorbidity information, BMD measurement data within the last 6 months, 24-hour urine and blood samples were taken from the patient and control groups. Results: FGF-23 and alpha klotho levels were significantly higher in the patient group. There was a positive correlation between FGF-23 and alpha klotho. A negative correlation was found between FGF-23 and urea levels while positive correlation was found between alpha klotho and L1-L4 T-score. Conclusions: These results suggested that there may be a relationship between sarcoidosis progression and FGF-23 and alpha klotho levels. Positive correlation between alpha klotho and L1-L4 T score in all groups suggests that alpha klotho may be associated with osteoporosis.